EARTH SYSTEM PROCESSES OF THE WALLACEA AND THEIR IMPLICATIONS TO THE INDONESIAN THROUGHFLOW AND BIOGEOGRAPHY - Sopaheluwakan, Jan (Marine Research in Indonesia, 2011)
The Wallacea with the total land area of 347,000 km designates a biogeographical group of Eastern Indonesian islands separated by deep water straits from the Asian and Australian continental shelves, and occupies a region with the world's most complex geological evolution and the accompanying extreme endemism. It also encloses remnants of emerged and submerged lands as well as dispersed and accreted island arcs and fragments of the continents resulting from a relatively continuous Cenozoic convergence of the Indo-Australian, Eurasia and Pacific-Philippine Sea plates. This paper discusses the Cenozoic spatial and temporal evolution of terranes in the region and explores how the Earth System Processes have eventually shaped up the Indonesian Throughflow and highlights the biogeographically unique and rich Wallacea. It will be demonstrated that the Wallace's line may have inherited an evolved multi-origin Early Cenozoic deep water barrier and the present Wallacea has been the resultant of significant Neogene convergent tectonics and significant modification by glacially-related sea level and climatic changes during the Quaternary. The gradual and systematic changes of the respective ocean regimes, the corresponding oceanometeorologic evolution, the emergence and disappearance of islands and land bridges, the dispersal and docking of some terranes have all resulted in the present configuration of the areas of endemism within the Wallacea. These changes correspond with the Neogene closure of the Indonesian Seaways, a narrow passage formed by the collision of the three major plates and the vanished pre-Cenozoic Tethyan ocean formed by the otherwise connected Indian and Pacific Oceans.